Exploring the synergistic effects of combining design thinking and project-based learning in a blended course (Journal of Applied Learning and Teaching, 2023)
This article presents an account of our experience in designing and implementing a course titled "Integration Project 3", in which we combined design thinking and project-based learning approaches. The course, conducted between March and June 2023, involved twelve undergraduate students from the Department of Technology in Educational Design at the Federal University of São Paulo situated in São Paulo, Brazil. Our research objective aimed to elucidate the synergistic effect of combining both approaches. Employing a mixed-method research design, we collected data from the students’ project website, from focus group activities and from a questionnaire. We conducted a systemic analysis utilizing causal loop diagrams. The findings of our study are as follows: 1) The implementation of design thinking methodology in addressing challenges faced by community partners not only motivated the students to learn but also facilitated the development of their problem-solving skills. 2) The integration of project-based learning and design thinking methodologies engendered the development of students’ project management skills and facilitated the application of acquired knowledge across various academic disciplines, thereby promoting interdisciplinary learning. 3) The students’ determination to work on real-life project tasks was influenced positively by their motivation to learn and negatively by the stress due to real-life project constraints.